Desain Interaksi Aplikasi Diskusi-Belajar Mengadopsi Media Sosial Memanfaatkan Prinsip Desain Nielsen - Andhika Giri Persada (Faculty of Industrial Technology Universitas Islam Indonesia, 2019)
E-Learning has been used as one of media that is used in the online-based learning process. Regarding to the fact about social media utilization by students, ideas are generated by adopting interactions from social media. Social media had proven able to attract various users, such as students. Utilization of mobile-based device, improve student's interest to use social media. Based on those facts, this study aims to design the interaction which is adopted from social media, named Diskusi-Belajar. There are two fundamental behind the reasons choosing social media as subject. First, social media had been proven able to attract users to communicate each other interactively. Second, social media has intuitive flow of interaction and interface which making it easier to be used. In this study, elements of the social media were converted into interaction design of Diskusi-Belajar. Interaction design is produced on mobile-based platform. In order to ensure usability quality, ten principles of the Nielsen's design are used as a guideline. Five evaluators are involved to measure interaction design and generated three times iterations. Conclusions of the study is, although not all Nielsen's design principles are accommodated, the elements which are generated from previous studies have succesfully implemented in Diskusi-Belajar and produce good usability.